B7-H3-Induced Signaling in Lung Adenocarcinoma Cell Lines with Divergent Epidermal Growth Factor Receptor Mutation Patterns. (24th December 2020) - Ding, Meng; Liao, Haixiu; Zhou, Nannan; Yang, Ying; Guan, Shihe; Chen, Liwen
Abstract : The cosignal molecule B7-H3 is gaining attention due to its abnormal expression and abundant signal transduction in many types of malignancies. B7-H3-induced signaling includes at least three cascades: PI3K/AKT, JAK2/STAT3, and Raf/MEK/ERK1/2, which are also involved in epidermal growth factor receptor- (EGFR-) triggered signaling in lung adenocarcinoma cells. However, the correlation between B7-H3-induced signaling and EGFR signaling, and between B7-H3-targeted immunotherapy and EGFR-targeted therapy in lung adenocarcinoma, remains to be elucidated. Herein we find that knockout of B7-H3 gene decreased cell survival and increased EGFR-tyrosine kinase inhibitor gefitinib susceptibility of both H3255 and HCC827 cells, two lung adenocarcinoma cell lines harboring EGFR L858R (exon 21) and Del E746-A750 (exon 19) mutations, respectively. B7-H3 deletion resulted in dramatic reduction of phosphorylation level of AKT and STAT3 in H3255 cells while having mild-to-moderate suppression on AKT, STAT3, and ERK1/2 in HCC827 cells. Gefitinib had similar effects with B7-H3 deletion both in H3255 and HCC827 cells. Furthermore, B7-H3 ablation had significant synergistic effects with gefitinib in HCC827 cells. Collectively, our study reveals B7-H3-induced signaling in lung adenocarcinoma cell lines with divergent EGFR mutations, and a translational potential of combined targeted therapy of B7-H3 and EGFR in lung adenocarcinoma with EGFR Del E746-A750 mutation.